Renewable biofuels : bioconversion of lignocellulosic biomass by microbial community - Rana, Vandana; Rana, Diwakar (Springer, 2017)
This book offers a complete introduction for novices to understand key concepts of biocatalysis and how to produce in-house enzymes that can be used for low-cost biofuels production. The authors discuss the challenges involved in the commercialization of the biofuel industry, given the expense of commercial enzymes used for lignocellulose conversion. They describe the limitations in the process, such as complexity of lignocellulose structure, different microbial communities' actions and interactions for degrading the recalcitrant structure of lignocellulosic materials, hydrolysis mechanism and potential for bio refinery. Readers will gain understanding of the key concepts of microbial catalysis of lignocellulosic biomass, process complexities and selection of microbes for catalysis or genetic engineering to improve the production of bioethanol or biofuel.
Keywords: Biomass energy.; Waste products as fuel.; Lignocellulose -- Biotechnology.; elektronické knihy; electronic books